2017
DOI: 10.1094/pdis-03-17-0435-re
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction: The Greatest Obstacle in Precise Determination of Rice Sheath Blight Resistance in the Field

Abstract: Rice sheath blight (SB) is the most serious rice disease in China. Resistance of rice to SB is a quantitative trait that is easily influenced by the environment; however, the extent of environmental influence on SB field resistance is still poorly understood. To identify rice genotype by environment interactions for SB resistance, 211 rice genotypes originating from 15 countries were planted and evaluated for SB field resistance in six different environments between 2012 and 2016 after inoculation with the SB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Moreover, our previous study [36] observed that the phenotypic diversity of several agronomic traits was comparable to that of populations with larger population sizes [48][49][50], or even higher for some agronomic traits. Ting's core collection consists of rice landraces that are considerably easier to utilize than wild rice in rice breeding because they have more abundant genetic diversity and remain in an intermediate stage between wild rice and cultivars in their domestication histories [37]. Ting's core collection shows a less complicated population structure, a shorter LD decay distance, and a lower kinship value than other populations utilized in rice GWAS [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, our previous study [36] observed that the phenotypic diversity of several agronomic traits was comparable to that of populations with larger population sizes [48][49][50], or even higher for some agronomic traits. Ting's core collection consists of rice landraces that are considerably easier to utilize than wild rice in rice breeding because they have more abundant genetic diversity and remain in an intermediate stage between wild rice and cultivars in their domestication histories [37]. Ting's core collection shows a less complicated population structure, a shorter LD decay distance, and a lower kinship value than other populations utilized in rice GWAS [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ShB resistance was estimated by one trait, i.e., lesion length/plant height (LL/pH), which had been utilized in previous studies [20,30,37]. It appears that LL/pH is the most applicable method for phenotyping ShB resistance within Ting's core collection because pH can affect the development of ShB pathogens in rice plants and influence eventual phenotypic outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeng et al . (2017) studied the environmental effect on disease progression among 169 genotypes and observed a highly significant ( P < 0.0001) effect. A positive correlation between RLH and DS was observed.…”
Section: Discussionmentioning
confidence: 99%